Pheromone‐binding proteins based phylogenetics and phylogeography of Maruca spp. from Asia, Africa, Oceania, and South America - Periasamy Malini; Srinivasan Ramasamy; Roland Schafleitner; Krishnan Muthukalingan (Ecology and Evolution)
Abstract Variations in the functional response of legume pod borer (Maruca vitrata) populations to sex pheromone blends were observed in Asia and Africa. Hence, this study was carried out to understand the differences in pheromone‐binding proteins (PBPs) among Maruca populations in Asia, Africa, Oceania, and South America. A de novo transcriptome assembly was adopted to sequence the entire transcribed mRNAs in M. vitrata from Taiwan. The raw‐sequence data were assembled using homologous genes from related organisms in GenBank to detect M. vitrata PBPs (MvitPBPs). Sections of the cDNA of MvitPBP of different length were used to design primers to amplify the full‐length cDNA of PBPs. All three PBP sequences comprised three exons interspersed by two introns. In total, 92 MvitPBP1 haplotypes, 77 MvitPBP2 haplotypes, and 64 MvitPBP3 haplotypes were identified in 105, 98, and 68 Maruca individuals, respectively. High pairwise FST values (0.41–0.73) and phylogenetic analyses distinguished the putative Maruca species in South America from those occurring in rest of the world, and possibly two putative subspecies in Asia and Africa. The haplotype networks and Automatic Barcode Gap Discovery analyses also confirmed these results. The negative Tajima's D and Fu's FS values showed the recent demographic expansion of Maruca populations. Thus, this study confirmed the presence of different Maruca species and/or subspecies in different continents based on the diversity within PBP genes. Additional sampling and studies are suggested for Oceania and South America. The genetic differences among Maruca populations should be carefully considered while using sex pheromone lures and bio‐control agents.